2011
DOI: 10.1051/0004-6361/201117404
|View full text |Cite
|
Sign up to set email alerts
|

Was the “naked burst” GRB 050421 really naked?

Abstract: Context. A few long gamma-ray bursts such as GRB 050421 show no afterglow emission beyond the usual initial steep decay phase. It has been suggested that these events correspond to "naked" bursts that occur in a very low density environment. We reconsider this possibility in the context of various scenarios for the origin of the afterglow. Aims. In the standard model where the afterglow results from the forward shock as well as in the alternative model where the afterglow comes from the reverse shock, we aim t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…The prompt emission is associated with internal shocks and the high latitude emission is in excellent agreement with XRT data (see Fig. 2 in Hascoët et al 2011).…”
Section: Internal Shockssupporting
confidence: 82%
See 1 more Smart Citation
“…The prompt emission is associated with internal shocks and the high latitude emission is in excellent agreement with XRT data (see Fig. 2 in Hascoët et al 2011).…”
Section: Internal Shockssupporting
confidence: 82%
“…As a last example, the "naked burst" GRB 050421 is a good case of a GRB with a variable light curve followed by an early steep decay that was well observed by the XRT because of its especially long duration (Godet et al 2006). This burst was modeled in detail by Hascoët et al (2011). The prompt emission is associated with internal shocks and the high latitude emission is in excellent agreement with XRT data (see Fig.…”
Section: Internal Shockssupporting
confidence: 72%
“…These features are not explained by the standard forward shock model (Meszaros & Rees 1997;Sari et al 1998), and it was proposed that the observed afterglow is produced by a long-lived reverse shock inside the GRB ejecta (Uhm & Beloborodov 2007;Genet et al 2007). The dynamics and emission of the reverse shock are particularly sensitive to the structure of the ejecta (the distribution of its Lorentz factor, density, and magnetic fields) which may explain the rich phenomenology of the early afterglow (Hascoët et al 2011(Hascoët et al , 2012Uhm et al 2012;Hascoët et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been extended by Genet et al (2007); Hascoët et al (2011Hascoët et al ( , 2012Hascoët et al ( , 2014 to include the deceleration phase. This allows to follow the forward shock in the external medium and the reverse shock in the ejecta.…”
Section: Ballistic Modelmentioning
confidence: 99%